Phenotypic Identification and Antibiotic Susceptibility Pattern of AmpC beta-Lactamase Producing Escherichia coli and Klebsiella pneumoniae Isolated from Urinary Tract Infections from a Tertiary Care Hospital of Rawalpindi, Pakistan - Nadia Saad; Tehmina Munir; Maliha Ansari; Mehreen Gilani; Mahwish Latif; Amira Haroon (Pasteur Institute of Iran, 2014)
Introduction: This study is aimed to compare phenotypic test methods and determine antibiotic susceptibility pattern of AmpC beta-lactamase producing uropathogenic Escherichia coli and Klebsiella pneumoniae in clinical isolates. Method: E. coli and K. pneumoniae were identified by standard microbiological procedures. Screening of AmpC beta-lactamase production was done by using cefoxitin disc (30 µg) showing inhibition zone diameter of <18 mm. Then, screen-positive isolates were subjected to Disc Approximation Test (DAT) and three dimensional extract test (3-DET) methods. Antibiotic susceptibility testing was performed by Kirby Bauer Disc diffusion technique. Results: A total of 120 Gram Negative Rods (GNRs) were included in the study. Amongst them cefoxitin resistant isolates were 68.33% (n=82/120). In these 82 isolates, E. coli were n=57 (69.51%) and K. pneumoniae were n=25 (30.48%). DAT identified 52.43% of AmpC beta-lactamase producing isolates, sensitivity of DAT was found to be 88% with 92% specificity, Positive Predictive Value of 92.68%, Negative Predictive Value of 87.80%, and Diagnostic Accuracy of 90.24%. Antibiotic susceptibility testing by Kirby Bauer Disc diffusion technique showed that carbapenems (meropenem) and tigecycline were of higher therapeutic effects against these resistant pathogens. Conclusion: Introducing simple tests like DAT in the laboratories can control the spread of AmpC beta-lactamase harboring organisms. Carbapenems (meropenem) and tigecycline are of suitable therapeutic effect against these resistant pathogens.